PENGARUH FASILITAS BELAJAR, TEKNOLOGI INFORMASI, PERSEPSI KOMPETENSI PEDAGOGIK GURU, DAN MOTIVASI BELAJAR TERHADAP PERSEPSI HASIL BELAJAR SISWA DI SMPK XYZ JAKARTA BARAT - Yules Gustaf Messa; Innocentius Bernarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to prove the influence of learning facilities, information technologyutilization, teachers' perceptions of pedagogical competence, and learningmotivation on students' perceptions of learning outcomes. The analysis resultsindicate that the standardized path coefficients (Standardized Path Coefficient) forlearning facilities (0.457), information technology (0.293), and learning motivation(0.158) are positive and significant in influencing students' perceptions of learningoutcomes. Meanwhile, the standardized path coefficient for teachers' perceivedpedagogical competence (-0.099) was found to have no significant positiveinfluence on students' perceptions of learning outcomes in the context of this study.These findings underscore the importance of optimizing facilities and technology, aswell as sustained efforts to cultivate student motivation, in shaping students' positiveperceptions of their achievements. Further implications are discussed for practicalrecommendations and future research.